2010
DOI: 10.1055/s-0030-1250385
|View full text |Cite
|
Sign up to set email alerts
|

Protective, Antioxidative and Antiapoptotic Effects of 2-Methoxy-6-Acetyl-7-Methyljuglone fromPolygonum cuspidatumin PC12 Cells

Abstract: Much correlative evidence indicates that the oxidative modification of protein by reactive oxygen species (ROS) is involved in normal aging as well as the pathogenesis of neurodegenerative diseases such as Alzheimer's disease. In this study, we explored the antioxidative and neuroprotective effects of a naphthoquinone, 2-methoxy-6-acetyl-7-methyljuglone (MAM), purified from the dried rhizome of POLYGONUM CUSPIDATUM (Chinese name Hu-Zhang). Pretreatments with MAM (24 h) were investigated for their protective ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 33 publications
1
13
0
1
Order By: Relevance
“…This compound may act as a potent antioxidant which significantly interferes with the apoptotic event [33]. …”
Section: Discussionmentioning
confidence: 99%
“…This compound may act as a potent antioxidant which significantly interferes with the apoptotic event [33]. …”
Section: Discussionmentioning
confidence: 99%
“…In Korea, people maintain oral health by using Polygonum cuspidatum (Polygonaceae) because of its efect in reducing oral microorganisms; Koreans also use P. cuspidatum in the treatment of arthritis and urinary diseases [37]. P. cuspidatum extract contains alkaloids, phenolics, and sterol/terpenes and induces biological activities such as anti-inlammation, antioxidation, and anticancer efects [38].…”
Section: Reactive Oxygen Species (Ros) and Lung Cancer Therapymentioning
confidence: 99%
“…28,29 Euclea natalensis extract alone may be an alternative product to protect oral health and prevent dental caries, 13 tooth wear and dentinal sensitivity. 31 For this reason, the effect of the chemical properties of Euclea natalensis as modifying factors for dental erosion should be explored in future investigations.…”
Section: Euclea Natalensismentioning
confidence: 99%
“…10 A study using histochemical analysis revealed the presence of naphthoquinones and polyphenols (such as flavonoids and tannins) in the root of the Euclea natalensis. 12,28,29 According to the literature presented, 28,29 the therapeutic effect of Euclea natalensis extract could be attributed to matrix metalloproteinases inhibition in the dentin. This may be justified, because the hardness analysis showed that there was a higher loss of hardness in the Euclea natalensis group, which, in turn, indicates the possibility of the collagen fiber structure having some flexibility.…”
mentioning
confidence: 99%